1980
DOI: 10.1111/j.1476-5381.1980.tb10960.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Distribution in the Rat: Temporal Relationship Between Tissue Levels and Blood Pressure Response

Abstract: 1 The time course of the distribution of clonidine (20 pg/kg, i.v.) was determined in the rat by use of a sensitive and specific radioimmunoassay, and was compared with the hypotensive response following this dose.2 Levels of clonidine were determined in tissues at 2 min, corresponding to the beginning of the hypotensive phase of the drug, and then at 10, 30 and 120 min during recovery of blood pressure to the pre-dose level. The peak tissue concentrations of clonidine were found at 2 min, after which they dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…This time frame is consistent with the pharmacokinetic properties of clonidine reported by [29,30]: clonidine dosed at 0.25 mg/kg peaks in the brain within 2 min and disappears at an average half-life rate of 70 min.…”
Section: Resultssupporting
confidence: 90%
“…This time frame is consistent with the pharmacokinetic properties of clonidine reported by [29,30]: clonidine dosed at 0.25 mg/kg peaks in the brain within 2 min and disappears at an average half-life rate of 70 min.…”
Section: Resultssupporting
confidence: 90%
“…There were at least 3 days (72 hours) between the intracranial injections. The half-lives of clonidine, dexmedetomidine, propranolol and prazosin are between 1 and 2 hours and therefore all the drugs will be metabolized after a 72-hour period (Conway and Jarrott, 1980; Elghozi et al, 1979; Hamilton et al, 1985; Salonen, 1989). The rats were left undisturbed in the vivarium on days that they were not tested.…”
Section: Methodsmentioning
confidence: 99%
“…administration. Conway & Jarrott (1980) found that the administration of clonidine (20,ugkg-', i.v. ) led to a rapid distribution, with the highest levels being obtained in all the tissues 2min after the injection.…”
Section: Discussionmentioning
confidence: 99%